2009
DOI: 10.1016/j.immuni.2009.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Early T Cell Receptor Signaling Regulate the Pathway of Lytic Granule Delivery to the Secretory Domain

Abstract: SUMMARY Cytolytic granule mediated killing of virus-infected cells is an essential function of cytotoxic T lymphocytes. Analysis of lytic granule delivery shows that the granules can take long or short paths to the secretory domain where they are released. Both paths utilize the same intracellular molecular events, which have different spatial and temporal arrangements in each path and are regulated by the kinetics of downstream Ca2+ mediated signaling. Rapid and robust signaling causes swift granule concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
167
0
4

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(190 citation statements)
references
References 44 publications
16
167
0
4
Order By: Relevance
“…In addition, long lasting NK cell/target cell couples did not lead to target cell lysis, thus further diminishing killing at the population level. Here sustained strong and stable interface actin accumulation could impede the myosin-dependent transport of cytolytic granules through the actin cortex (31) or translocation of granules from the periphery of the interface to its center (32). As an important future challenge, signaling events that downregulate the initially strong polarization in efficient cytolysis need to be identified.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, long lasting NK cell/target cell couples did not lead to target cell lysis, thus further diminishing killing at the population level. Here sustained strong and stable interface actin accumulation could impede the myosin-dependent transport of cytolytic granules through the actin cortex (31) or translocation of granules from the periphery of the interface to its center (32). As an important future challenge, signaling events that downregulate the initially strong polarization in efficient cytolysis need to be identified.…”
Section: Discussionmentioning
confidence: 99%
“…There is currently substantial excitement in elucidating the molecular mechanisms of LG polarization to the secretory domain of the CTL-target contact zone (4,24). Jenkins et al (25) have shown that the strength of the TCR signal is exceptionally important for LG accumulation at the IS, and Beal et al (26) unmasked the kinetics of a short and long path of LG to the synapse.…”
mentioning
confidence: 99%
“…The SNARE Synaptobrevin 2 facilitates the fusion of lytic granules with the plasma membrane of human CTLs [62]. The strength of the TCR signal controls the focal point for granule exocytosis, permitting release at the pSMAC if the signal is weak instead of delivery to the secretory domain at the cSMAC [63]. Upon centrosomal relocalization, lytics granules are delivered to the IS by a complex formed by kinesin-1/Rab27a/Slp3 [64], suggesting lytic granules depend on microtubules.…”
Section: Late Endosomes: the Multivesicular Bodiesmentioning
confidence: 99%